Implementation of Islamic Religious Education Learning to Improve Emotional Intelligence of Students at Roudhotul Athfal Darul Ulum Mancilan, Pasuruan City - Mustabsyiroh, Mustabsyiroh; Rofiq, Ainur; Hamza, Hichem (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2024)
Implementation is an action or implementation of a plan that has been prepared carefully and in detail, usually carried out after the planning is considered perfect. Islamic Religious Education is a process of transforming knowledge and internalizing Islamic values ​​to develop the basic potential of students to achieve balance in various aspects of life. The goal is to prepare a generation of Muslims with noble morals to build a prosperous, harmonious, and sustainable society according to Allah's law. This study uses a qualitative method with a case study approach, which was conducted at Roudlotul Athfal Darul Ulum Mancilan, Pasuruan. This study aims to describe Islamic Religious Education at Roudlotul Athfal Darul Ulum Mancilan, Pasuruan City, and to describe the implementation of Islamic Religious Education learning in improving students' emotional intelligence at the institution. The research findings show that interactive and integrative Islamic Religious Education learning has a positive impact on the development of students' emotional intelligence, including their ability to identify, manage, and express emotions adaptively. Parental involvement also plays an important role in strengthening this positive impact. Early childhood education that is implemented well is expected to produce quality individuals, while if ignored, children have the potential to face problems in the future.